Recycled wind turbine blades as a feedstock for second generation composites. (June 2018) - Mamanpush, Seyed Hossein; Li, Hui; Englund, Karl; Tabatabaei, Azadeh Tavousi
Highlights: Finding feasible and promising strategy to recycle the wind turbine blade. Considering low cost innovative recycling method for recycling thermoset composites. Recycled wind turbine blade materials as a feedstock of second generation composites. Abstract: With an increase in renewable wind energy via turbines, an underlying problem of the turbine blade disposal is looming in many areas of the world. These wind turbine blades are predominately a mixture of glass fiber composites (GFCs) and wood and currently have not found an economically viable recycling pathway. This work investigates a series of second generation composites fabricated using recycled wind turbine material and a polyurethane adhesive. The recycled material was first comminuted via a hammer-mill through a range of varying screen sizes, resinated and compressed to a final thickness. The refined particle size, moisture content and resin content were assessed for their influence on the properties of recycled composites. Static bending, internal bond and water sorption properties were obtained for all composites panels. Overall improvement of mechanical properties correlated with increase in resin content, moisture content, and particle size. The current investigation demonstrates that it is feasible and promising to recycle the wind turbine blade to fabricate value-added high-performance composite.